Sayembara Misuhi Pandemi: Wujud Katarsis dalam Kreativitas Kebahasaan di Tengah Gelombang Pandemi Covid-19 - Prakoso, Imam (Jayapangus Press, 2025)
This study examines the variations in Javanese swear words created in a competition titled